Diagnostic Performance of Smear Microscopy and Xpert MTB/RIF Versus MGIT Culture in Republic of Congo - Ornelle Elion Assiana Darrel; Arnold Elouma Ndinga Murphy; Hermeland Mouzinga Freisnel; Okemba-Okombi Franck-Hardin; Christevy Vouvoungui Jeannhey; Ahombo Gabriel; Ntoumi Francine (International Journal of Clinical Microbiology, 2025)
In the Republic of the Congo, tuberculosis (TB) remains a major public health concern. Although the GeneXpert MTB/RIF assay is the WHO-recommended first-line diagnostic test, smear microscopy is still used for treatment monitoring and in facilities where molecular testing is limited. Evaluating the diagnostic accuracy of smear microscopy compared to GeneXpert and MGIT culture is essential to guide diagnostic strategies and strengthen TB control in the country. A cross-sectional study was conducted among 92 presumptive pulmonary TB patients at Makelekele Hospital. Sputum samples were analyzed by smear microscopy, GeneXpert MTB/RIF, and MGIT culture. Sensitivity, specificity, positive and negative predictive value were calculated for smear microscopy and GeneXpert, using culture as the reference standard. Culture detected more Mycobacterium tuberculosis than microscopy (49% vs. 32%, P<0.001). Smear microscopy showed a sensitivity of 58% (95% CI: 43–71%) and specificity of 92% (95% CI: 80–97%). GeneXpert detected more MTB (62% vs. 49%, P<0.001) with a sensitivity of 98% (95% CI: 89–100%) and specificity of 72% (95% CI: 58–83%). GeneXpert showed superior sensitivity for TB detection, while microscopy remained specific. Expanding GeneXpert testing across the Republic of the Congo will improve TB management.
Keywords: Tuberculosis